2000
DOI: 10.1006/dbio.2000.9824
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Expression of Nuclear Factor-κB Inhibits Epithelial Growth and Branching in the Embryonic Chick Lung

Abstract: It is becoming increasingly recognized that the ubiquitous, inducible transcription factor nuclear factor-kappaB (NF-kappaB) is involved in developmental processes. For example, NF-kappaB acts as a mediator of epithelial-mesenchymal interactions in the developing chick limb. We investigated the role of NF-kappaB in directing the branching morphogenesis of the developing chick lung, a process which relies on epithelial-mesenchymal communication. High level expression of relA was found in the mesenchyme surround… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 69 publications
2
39
1
1
Order By: Relevance
“…Disrupting NF-B activity in embryonic limb mesenchyme impaired limb outgrowth and resulted in aberrant morphology of the apical ectodermal ridge (Bushdid et al, 1998). Similar experiments in embryonic lung demonstrated that activity of NF-B in lung mesenchyme is necessary for proper budding and growth of the adjacent lung epithelium (Muraoka et al, 2000). Based on data derived from these model systems, it is possible that NF-B activity in the mammary epithelium is regulated by paracrine signals emanating from the adjacent stroma, or even neighboring epithelial cells, to control epithelial branching and proliferation during early mammary gland morphogenesis.…”
Section: Nf-b In Mammary Proliferationmentioning
confidence: 85%
See 2 more Smart Citations
“…Disrupting NF-B activity in embryonic limb mesenchyme impaired limb outgrowth and resulted in aberrant morphology of the apical ectodermal ridge (Bushdid et al, 1998). Similar experiments in embryonic lung demonstrated that activity of NF-B in lung mesenchyme is necessary for proper budding and growth of the adjacent lung epithelium (Muraoka et al, 2000). Based on data derived from these model systems, it is possible that NF-B activity in the mammary epithelium is regulated by paracrine signals emanating from the adjacent stroma, or even neighboring epithelial cells, to control epithelial branching and proliferation during early mammary gland morphogenesis.…”
Section: Nf-b In Mammary Proliferationmentioning
confidence: 85%
“…For example, the increase in branching of the IB␣-deficient epithelium may be a direct result of increased proliferation, and the reduced levels of ECM expression may be due to heightened proliferation in the IB␣-deficient epithelium. Correlations between levels of proliferation and branching morphogenesis have been observed in other branching organ systems, including lung, another organ that uses NF-B to establish epithelial branching patterns through epithelial-mesenchymal interactions (Serra et al, 1994;Muraoka et al, 2000). Alternatively, the reduction of ECM may be a direct effect of increased NF-B activity.…”
Section: Nf-b In Mammary Proliferationmentioning
confidence: 97%
See 1 more Smart Citation
“…In the embryonic chick lung, hyperactivation of NF-B by the expression of IKK50, a constitutively active isoform of human IKK2, resulted in intense mesenchymal TGF-␤1 expression (28). Treatment with RelA antisense oligonucleotides inhibited TGF-␤1 mRNA expression in fibrosarcoma cells (19) and in monocytes from patients with idiopathic myelofibrosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…Physical stretching of lung epithelial cells activates NF-kB (Harding and Hooper, 1996), which enhances maturation of lung epithelial cells during embryogenesis in mouse (Londhe et al, 2008). In chicken lung, NF-kB activity in the mesenchyme also has a role during morphogenesis of lung branching (Muraoka et al, 2000). Similarly, the level of tensile prestress (isometric tension) generated by Rho-dependent changes in cytoskeletal contractility affects lung branching morphogenesis in mice (Moore et al, 2002;Moore et al, 2005).…”
Section: Lungmentioning
confidence: 99%